we first need to bring both fractions to the same denominator, so we will multiply the first one by x+4. (because (x-4)(x+4)=x^2-16) (x-6)(x+4)/(x^2-16) + 16/(x^2-16)=0 (x-6)(x+4)+16=0 (if a fraction is equal to 0, the numerator...
we first need to bring both fractions to the same denominator, so we will multiply the first one by x+4. (because (x-4)(x+4)=x^2-16) (x-6)(x+4)/(x^2-16) + 16/(x^2-16)=0 (x-6)(x+4)+16=0 (if a fraction is equal to 0, the numerator...
log in base 2 of x = y if we rewrite the expression in exponential form: 2^y= x so x is 2^(1212...)
The formula for the general term of an arithmetic sequence is: an=a1+(n-1)d If we susbtitute all the values: a20=3+(20-1)7=3+19*7=136
I assume if it is an equation, it should be set equal to some other expression? What you'd do is square both sides, because that gets you rid of the square root. a simple example sqrt(x^4)=4 therefore x^4=16 (after raising both sides to the second power)
1) 31+ 0.16m=47.96 .16m=16.96 m=106 miles b) 2) y=18x-x^2 is a parabola that opens down with a maximum at its vertex. The x coordinate of the vertex is -b/2a where a b c are the coefficients of the polynomial y=ax^2+bx+c In our case...
Let's start with f(x). f(x)=(9x+2)/3x with a domain of all real number except 0. (we cannot have 0 at the denominator) In order to find out the inverse, set the function =y, and solve for x (9x+2)/3x=y/1 Let's...
Even though it is not actually accurate in the 21st century, we generally consider: P(having a boy)=1/2 P(having a girl)=1/2 a) P(1 boy)=P(Boy,Girl,Girl)+P(Girl,Boy,Girl)+P(Girl,Girl,Boy)=1/2*1/2*1/2+1/2*1/2*/2+1/2*1/2*1/2=1/8+1/8+1/8=3/8 b)P(at...
I hope my answer is not coming too late, but print out a formula sheet for yourself and you'll remember conic sections much more easily after solving problems like that. So, the vertices are at (0,2) (0,-2) which means the transverse axis has length of 4, so the semi-transverse...
Let v=average speed, d=distance, t=time => v=d/t d=v*t First month: 150=v*t Second month: 150=(v-5)(t+1) We have two equations and two unknowns, so we can solve this system by using substitution. From the first equation ...
As I've mentioned in the previous problem, the general equation of a parabola that opens up or down is: y=a(x-h)^2+k If a is positive, it'll open up. If a is negative, it'll open down. a.The vertex, (h,k) is in our case (2,-1) b.The...
Hi, Jarod! The vertex form of a parabola that opens either up or down is: y=a(x-h)^2+k where (h,k) is the vertex of your parabola. If a is positive the parabola will open up/to the right, and if a is negative it will open down/to...
I assume you are asking about the point-slope form of the equation. Let's first calculate the slope: m=(y2-y1)/(x2-x1)=(-5-5)/(-1-0)=-10/-1=10 <-slope The point slope formula is: y-yp=m(x-xp) where P(xp, yp) is a point on our...
The decay factors are (1-30/100) and (1-20/100), where 30/100 and 20/100 stands for the actual percentages that are taken off of the initial price. Therefore, the final price will be $100*(1-.30)*(1-.20)=$56 dollars. Multiplying by (1-.20) after we've already...